The Extent to Which Social Studies Teachers Employ Lateral and Design Thinking in Architectural Education: An Exploratory Study from Their Perspective - Al-Ghawi, Zouwaina Khalaf; Al Najar, Noor Ahmed (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the extent to which social studies teachers employ lateral and design thinking in architectural education. To achieve this, the researcher adopted a descriptive analytical approach and developed a questionnaire consisting of two dimensions: the first included 10 items addressing the extent of employing lateral thinking in architectural education, and the second included 10 items addressing the use of design thinking in the same context. The instrument was administered to a sample of 26 male and female social studies teachers in the Sultanate of Oman. The findings revealed a low level of implementation of both lateral and design thinking in architectural education. Furthermore, no statistically significant differences were found between the levels of employing either type of thinking. Accordingly, the researcher recommends the integration of lateral thinking and design thinking into architectural education, given their essential role in fostering advanced creative thinking skills and enhancing students’ ability to analyze forms and spaces from a critical aesthetic perspective. Such integration contributes to preparing a generation of learners with refined architectural visual sensitivity, capable of appreciating and understanding architectural beauty in alignment with future skill requirements.
Keywords: Lateral Thinking; Design Thinking; Architectural Education